Effects Of Oil Palm Plantation Tasks On Skeletal Muscle Activities - Nordin, Muhammad Nor Akmal (Universiti Sains Malaysia, 2022)
The purpose of this study was to look at and present the risk of work-related musculoskeletal disorders (WMSDs) in collecting activities as well as oil palm fronds pruning activities. Eight subjects with different experience in collecting and pruning oil palm were recruited to perform this task with different tools such as chisels, sickles as well as traditional tools for lifting palm fruit. Experiments were conducted in various types of techniques, namely loading the oil palm fruit by using manual methods where it is divided into two categories, namely the body is twisted and the body is bent forward. Traditional tools were used to assess body muscle activation in loading activities at different heights, the task of pruning palm fronds at three different heights and also pruning palm fronds using two different tools. In analyzing the subject’s motion, the inertial measurement units (IMU) from Xsens was used. Electromyography (EMG) sensors from iMotions were used to analyze upper body muscle activation. EMG electrodes in the bipolar arrangement were installed on eight body muscles (upper trapezius, middle trapezius, left and right biceps brachii, left and right middle deltoids, erector spinae longissimus and rectus femoris). Each subject experienced pain in certain parts of the body investigated. Improvements in the work environment are needed to reduce the risk of WMSD and fatigue among oil palm workers. Further studies with more workers in oil palm plantations are recommended for better effect measurement in explaining exposure to WMSD and muscle utilization.